Critical assessment of pendimethalin in terms of persistence, bioaccumulation, toxicity, and potential for long-range transport. (2nd January 2017) - Vighi, Marco; Matthies, Michael; Solomon, Keith R.
ABSTRACT: Pendimethalin (PND, CAS registry number 40487-42-1) is a dinitroaniline herbicide that selectively controls broad-leaf and grassy weeds in a variety of crops and in noncrop areas. It has been on the market for about 30 yr and is currently under review for properties related to persistence (P), bioaccumulation (B), and toxicity (T) in the European Union (EU). A critical review of these properties as well as potential for long-range transport (LRT) was conducted. Pendimethalin has a geometric mean (GM) half-life of 76–98 d in agriculturally relevant soils under aerobic conditions in the lab. The anaerobic half-life was 12 d. The GM for field half-lives was 72 d. The GM half-life for sediment-water tests in the lab was 20 d and that in field aquatic cosms ranged from 45 to 90 d. From these data PND is not persistent as defined in the Annex II of EC regulation 1107/2009. The GM bioconcentration factor for PND was 1878, less than the criterion value. This was consistent with lack of biomagnification or accumulation in aquatic and terrestrial food chains. The GM no-observed-effect concentration (NOEC) value for fish was 43 µg/L, and 11 µg/L for algae. These do not trigger the criterion value for toxicity. In air, the DT50 of PND was estimated to be 0.35 d, which is well below the criterion of 2 d for LRT under the United Nations Economic Commission for Europe (UNECE) Aarhus protocol. Modeling confirmed lack of LRT. Because of its volatility, PND may be transported over short distances in air and was found in samples in local and semiremote regions; however, these concentrations are not of toxicological concern. Unlike other current-use pesticides, PND has not been found in samples from remote regions since 2000 and there is no apparent evidence that this herbicide accumulates in food chains in the Arctic.